Filmes finos luminescentes de polissacarídeos com potencial atividade bactericida - Scapolan, Maria Izabel Xavier (2022)
Films based on polysaccharides produced by the Layer-by-Layer (LbL) technique have a simple method of obtaining, simple functionalization and the possibility of presenting antibacterial properties. Luminescent films can be used as coatings that exhibit a luminous response to the chemical environment and the use of Eu3+ as a spectroscopic probe can be useful to understand the formation and structure of these films. The present study aims to investigate the assembly process of LbL luminescent films using chitosan (CHI) and sodium alginate (ALG) as polyelectrolytes. Slide glass and polystyrene were used as substrates for the films. Polysaccharide solutions (10 mg/L) were used to manufacture samples with one, three and five bilayers. Eu3+ was added by two distinct methodologies: ex-situ (AC)nEu and in-situ, (ACEu)n. Besides, coordination and luminescent properties along with the ligant 2- tenoiltrifluoroacetone (tta 1 mmol/L). All films exhibit the CHI emission in 418 nm and the intraconfiguracional transition of Eu3+. The ex-situ deposition method produces films with more available ions capable to enhance the luminescent properties, for only the (AC)3Eu, (AC)5Eu and (AC)5Eutta samples presented the 5D0  7F2 emission more intensely than the ALG/CHI matrix. Samples with tta present higher emission lifetime and lower surface roughness due to the substitution of water molecules in the coordination sphere. The films with more layers and those obtained by the in-situ method exhibited higher homogeneity, hinting the Eu3+ layer post layer reticulation. The films produced in polystyrene substrates showed uniformity and reproductibility in the layer formation, with this being supported by elipsometry and quartz microbalance. The PS5Eu, PS5Eutta, PS10Eu and PS10Eutta samples presented antiadesive properties when interacting with gram-negative bacteria, such as Pseudomonas aerugonosa, and gram-positives as well, such as Staphylococcus aureus. Such property depends on the presence of Eu3+ and the organic ligant, due to the films’ changes in hidrophilicity and roughness. The produced materials have a great potential to be applied in several applications.